Mathematical model on the effects of global climate change and decreasing forest cover on seasonal rainfall in Northern Thailand - Chulin Likasiri (2018)
This research involves the study of the long-term behaviors of Northern Thailand rainfall as affected by changes to its forest area and the rise in global temperature. Global temperature and forest data are considered annually while rainfall data are considered seasonally to best capture the effects of severe weather hazards such as draught and flood. A differential equation model was developed and verified using the mean global temperature data collected annually during 1880-2010, Northern Thailand forest area data collecting during 1973-2008, and data on the daily amounts of rainfall in Northern Thailand during 1971-2011. The rise in global temperature as well as the decline in Northern Thailand's forest area can be, as shown in the paper, represented by logistic equations. Northern Thailand rainfall is, however, represented as a periodic function; hence, second order differential equation, of which the solution is periodic, is used to represent the rate of change in the amount of rainfall. In addition, by correlation analysis, the predator-prey terms of forest, global temperature and rainfall are presented in the models. All parameters in the models are validated by minimizing sum squared error. © 2013 Elsevier B.V.